Analisis parameter fisika kimia air pada lokasi karamba jaring tancap di Danau Tondano Kabupaten Minahasa Provinsi Sulawesi Utara - Sarif, Abdul J.; Kusen, Diane J.; Pangemanan, Novie P.L. (e-Journal BUDIDAYA PERAIRAN, 2019)
This research was to determine the current condition of the water physical chemical quality parameters at culture areas in Lake Tondano. The study  conducted at Lake Tondano Minahasa Regency, North Sulawesi Province.  Determination of the water physical and chemical qualitis was carried through field observation and laboratorium analysis at the Industrial Research and Standardization in Manado. Measurement and retrieval of physical and chemical parameter of water quality was done at culture site with high density, medium and small especially at Eris Village, Leleko Village and Toulour Village. Water temperature was 26oC - 29oC, brightness of 1.34-2.8 cm, depth of 4.23-11.8 m, acidity of 6.7-7.8 mg/L, dissolved oxygen, 2.75–6.31 mg/L, nitrate 0.00-1.58 mg/L, nitrite 0.00–0.027 mg /L, ammonia 0.00–0.292 mg/L and phosphate 0.02–0.721 mg/L.  The results showed that water quality of Lake Tondano still match the quality standard of water quality for fish cultivation except ammonia.Keywords: water quality, net cages, Lake Tondano